Genocide and resistance Nr. 47(1) - Banionis, Juozas; Jaskelevičius, Tadas; Buchaveckas, Stanislovas; Bubnys, Arūnas; Kripienė, Enrika; Burinskaitė, Kristina; Veilentienė, Audronė; Ereminas, Gintautas (Genocidas ir rezistencija, 2020)
Full Issue